LIBERDADE RELIGIOSA ENQUANTO INSTRUMENTO DE LUTA NO CONTEXTO DE GARANTIA DAS LIBERDADES: uma análise histórica do desafio da guarda de um dia de descanso religioso e sua guarida à luz do Direito Internacional e Nacional - Silva, Alda Fernanda Sodré Bayma (2015)
The protection of religious freedom under the Brazilian legal system now requires a new look meet the demands arising in the exercise of faith and their acts of worship, namely, rest days, ornaments, places of worship etc. Taking as its starting point the historical construction of the right to religious freedom as guarantees of legitimizing instrument in the midst of a pluralistic and democratic society, raises the prospect of religious rest day protection as bias to be safeguarded as a means of demonstration respect for diversity and the exercise of religious tolerance. While the Legislature is omitted on the scope and protection of religious rest day, the Judiciary Power come constantly creating and abridging rights making up clearly see through the case study of this work, which courts have diametrically opposed decisions, which sometimes they relate to the literalness of the law disregarding the fact that a fair decision must be based on arguments of principle that will make the decisions seek equality and justice. The example of the United States and European Union reinforce the discussion, since there are accommodation mechanisms that comply well with the role of mediators in the search for safeguarding the full exercise of religious freedom in those countries. It is not a perspective that goes against the pillars of formation of the secular State. Before, it is on a quest to give effect to the right of a minority that is still little heard.